Iron–PNP‐Pincer‐Catalyzed Transfer Dehydrogenation of Secondary Alcohols. Issue 13 (26th April 2019) - Budweg, Svenja; Wei, Zhihong; Jiao, Haijun; Junge, Kathrin; Beller, Matthias
Abstract: The well‐defined iron PNP pincer complex catalyst [Fe(H)(BH4 )(CO)(HNCH2 CH2 P( i Pr)2 2 ] was used for the catalytic dehydrogenation of secondary alcohols to give the corresponding ketones. Using acetone as inexpensive hydrogen acceptor enables the oxidation with good to excellent yields. DFT computations indicate an outer‐sphere mechanism and support the importance of an acceptor to achieve this transformation under milder conditions. Abstract : Catalytic dehydrogenation of secondary alcohols to the corresponding ketones is realized by using an iron pincer complex. Using acetone as a hydrogen acceptor enables the oxidation under mild conditions and low catalyst loading with excellent yields.